2014
DOI: 10.5739/jfpsij.8.66
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Actuator Displacement-Controlled System with Pump Switching–

Abstract: Displacement-controlled (DC) actuation has been under investigation by the authors' group since its conception in 1998 as a highly efficient alternative to its valve controlled counterpart. The major advantages of DC actuation include the complete elimination of losses due to resistive control and the recuperation of energy due to overriding loads. One obstacle for the introduction of DC actuation to the market is the increased machine production costs due to the one-pump-per-actuator requirement. To overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…This leads to lower working temperature, downsized combustion engines and reduction or potential elimination of the cooling requirements [100][101][102][103]. The authors in [104,105] suggested pump sharing between multiple actuators to decrease the overall cost of the hydraulic system. Further activities have been related to mode oscillation (similar to what was seen in Section 4.1.1) [106], active oscillation damping [107,108] and thermal modelling [109,110].…”
Section: E1-passive Valvesmentioning
confidence: 99%
“…This leads to lower working temperature, downsized combustion engines and reduction or potential elimination of the cooling requirements [100][101][102][103]. The authors in [104,105] suggested pump sharing between multiple actuators to decrease the overall cost of the hydraulic system. Further activities have been related to mode oscillation (similar to what was seen in Section 4.1.1) [106], active oscillation damping [107,108] and thermal modelling [109,110].…”
Section: E1-passive Valvesmentioning
confidence: 99%
“…To mention a few of these, this architecture was considered in relation to cranes in [3,4], wheel loaders in [5,6], and excavators in [7][8][9]. In the latter case, the power management with multiple drives was investigated [10,11]. This architecture maintains a proper drive stiffness as the lower chamber pressure is held at a certain level by the charge pump, which on the other hand induces certain losses as a result of its constant flow output.…”
Section: Variable Displacement Approachmentioning
confidence: 99%
“…Whereas displacement control at multi-cylinder/motor systems level has been considered for several years [45,46], enabling fairly simple inclusion of valve actuated low power functions, developments extending beyond standalone cylinder drives with variablespeed displacement units have only recently begun to emerge. These may allow both to downsize electric motors and for easy implementation of valves for low power functions.…”
Section: Introductionmentioning
confidence: 99%